The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/bot.0000000000002041
|View full text |Cite
|
Sign up to set email alerts
|

Large Individual Bilateral Differences in Tibial Torsion Impact Accurate Contralateral Templating and the Evaluation of Rotational Malalignment

Abstract: Objective: To determine individual bilateral differences (IBDs) in tibial torsion in a diverse population.Methods: Computed tomography scans of uninjured bilateral tibiae were used to determine tibial torsion and IBDs in torsion using 4 measurement methods. Age, sex, and self-identified race/ethnicity were also recorded for each subject. Mean tibial torsion and IBDs in torsion were compared in the overall cohort and when stratified by sex and race/ethnicity. Simple and multiple linear regression models were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 42 publications
2
7
1
Order By: Relevance
“…First, it provides an absolute value that reflects the actual rotation of the tibia rather than a proxy value or the requirement of the surgeon to compare relative radiographic overlap of anatomic structures. Even though large variation of anatomic tibial rotation exists within the population and even within an individual, 17,18 the absolute value is useful, particularly when the contralateral limb cannot be used as a reliable comparison. For example, in the setting of amputation, total knee or ankle arthroplasty, or deformity, the injured limb's rotation can be set to that of the population norm of approximately 30 degrees.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, it provides an absolute value that reflects the actual rotation of the tibia rather than a proxy value or the requirement of the surgeon to compare relative radiographic overlap of anatomic structures. Even though large variation of anatomic tibial rotation exists within the population and even within an individual, 17,18 the absolute value is useful, particularly when the contralateral limb cannot be used as a reliable comparison. For example, in the setting of amputation, total knee or ankle arthroplasty, or deformity, the injured limb's rotation can be set to that of the population norm of approximately 30 degrees.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the setting of amputation, total knee or ankle arthroplasty, or deformity, the injured limb's rotation can be set to that of the population norm of approximately 30 degrees. [17][18][19][20] It is important to interpret the results of this study with consideration of the strengths and limitations. The intraoperative measurements throughout the course of the study were performed by 3 orthopaedic traumatologists, improving the generalizability of this study with multiple observers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study reported here from Los Angeles (California, USA) included 195 scans with calculated rotations. 10 The mean external rotation was 27°, with a mean difference (IBD) of 5° between legs. A > 10° difference was present in 12.3% of reported cases, and was more likely if the reported baseline amount of torsion was higher.…”
Section: Tibial Rotation: Is There a Difference Between Legs? X-refmentioning
confidence: 99%